Integration of Thomson scattering and laser-induced fluorescence in ITER divertor. (5th July 2019) - Mukhin, E.E.; Kurskiev, G.S.; Gorbunov, A.V.; Samsonov, D.S.; Tolstyakov, S.Yu.; Razdobarin, A.G.; Babinov, N.A.; Bazhenov, A.N.; Bukreev, I.M.; Dmitriev, A.M.; Elets, D.I.; Koval, A.N.; et al.
Abstract: Divertor Thomson scattering (DTS) and laser-induced fluorescence (LIF) are both laser aided diagnostics well suited to combination with common probing and collecting optics that are the most sophisticated and expensive part of any ITER optical diagnostic system. The combination of DTS and LIF are used for simultaneous measurement of local electron ( T e, n e ), ion ( T i, n HeII ) and atom ( n HeI, n H(D, T) ) parameters and provide basic information on rates of electron and ion processes to allow basic understanding of the physics of divertor plasma detachment. The measured parameters permit the calculation of rates of ionization and recombination using T e, n e, T i, n i, n HeI and n H(D, T) ; emission intensity— T e, n e, n i, n HeI and n H(D, T) ; frictional force of the plasma flow due to collisions with neutrals— T i, n i, T 0, n HeI and n H(D, T) and pressure of the incoming plasma flow— T e, n e, T i and n i . The paper discusses the benefits of DTS and LIF integration, suggests new approaches to the estimation of DTS capability, LIF implementation and possibilities for further diagnostic development.